The Afghan-Pakistan Borderlands and Their Impact on Pakistan’s Security - Mukhit Assanbayev; Mohammad Talha; Muhammad Murtaza (Journal of Central Asian Studies, 2025)
The Afghanistan-Pakistan borderlands have a significant impact on the relationship between the two neighboring states, Afghanistan and Pakistan, as well as on Pakistan’s security. This border zone, known as the Durand Line, is not just a line on a map. It is the zone of interaction, conflict, negotiation, and hybridity that has become a haven for “Tehrik-e-Taliban Pakistan”, one of the extremist and terrorist organizations operating here over the past two decades. Today, Pakistan finds itself in a challenging position due to the periodic infiltration of “Tehrik-e-Taliban Pakistan” militants from Afghan territory and a renewed wave of violence in Khyber Pakhtunkhwa province, as well as in some other regions of Pakistan. The danger lies in the fact that the “Tehrik-e-Taliban Pakistan” utilizes Afghan territory to plan and execute operations within Pakistan. The purpose of this article is to analyze how borders with cross-border ethnic, social, and economic networks are continually constructed, maintained, and contested through policies, violence, and social practices. The theoretical framework is primarily grounded in the concept of borderlands theory and, to a lesser extent, in insurgency and counterinsurgency theories. It draws on a wide range of recent sources, highlighting the background and realities of the Afghanistan–Pakistan borderlands. The findings and insights, derived from a comparative and empirical content analysis of the Afghan-Pakistan borderlands, challenge traditional state-centric views and reveal how borderlands function as dynamic spaces of interaction, conflict, and identity negotiation.